2018
DOI: 10.1007/s10620-018-5262-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognosis of Subsequent Cholangiocarcinoma in Patients with Hepatic Resection for Bile Duct Stones

Abstract: Subsequent CCA developed in 2% of the patients with hepatic resection for benign BDS until 10 years and was associated with poorer prognoses than concomitant CCA. Future studies focused on the long-term surveillance for CCA in such patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…In a retrospective study by Zhang et al [34], in line with our result, hepatitis was found to be with poor prognosis in IHCC, while in the study by Zhou et al, hepatitis was a favorable prognostic factor [35]. The prognositic value of age was controversial, most study reported that age had no prognostic value in cholangiocarcinoma [34, 36–38]. Mavros et al and Kato et al found that older age was associated with worse prognosis [39, 40].…”
Section: Discussionsupporting
confidence: 79%
“…In a retrospective study by Zhang et al [34], in line with our result, hepatitis was found to be with poor prognosis in IHCC, while in the study by Zhou et al, hepatitis was a favorable prognostic factor [35]. The prognositic value of age was controversial, most study reported that age had no prognostic value in cholangiocarcinoma [34, 36–38]. Mavros et al and Kato et al found that older age was associated with worse prognosis [39, 40].…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, sex was an independent prognostic factor in the univariate analysis ( P <0.001), and it was not statistically significant in the multivariate model ( P =0.79). Previous studies have shown that sex is an independent prognostic factor and that male patients have shorter survival times than female patients ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study by Zhang et al [34] , in line with our result, hepatitis was found to be with poor prognosis in IHCC, while in the study by Zhou et al, hepatitis was a favorable prognostic factor [35] . The prognositic value of age was controversial, most study reported that age had no prognostic value in cholangiocarcinoma [34,[36][37][38] . Mavros et al and Kato et al found that older age was associated with worse prognosis [39,40] .…”
Section: Discussionmentioning
confidence: 99%